Psychological Characteristics of the Formation of Business Communication Employees of Local Authorities - Kurenchuk, L. S. (Psychological Prospects Journal, 2011)
In the article grounded the use of the socialpsychological training in forming of business intercourse of workers of local organs of executive power as an active method of studies, principles of his application are exposed.